Mathematical modelling of mass transfer in multi-stage rotating disc contactor column - Arshad, Khairil Anuar; Talib, Jamalludin; Maan, Normah (Universiti Teknologi Malaysia, 2006)
In this study, the development of an improved forward model for the mass transfer process in the Rotating Disc Contactor (RDC) column was carried out. The existing mass transfer model with constant boundary condition does not accurately represent the mass transfer process. Thus, a time-varying boundary condition was formulated and consequently the new fractional approach to equilibrium was derived. This derivation initiated the formulation of the modiÂ¯ed quadratic driving force, called Time-dependent Quadratic Driving Force (TQDF). Based on this formulation, a Mass Transfer of A Single Drop (MTASD) Algorithm was designed, followed by a more realistic Mass Transfer of Multiple Drops (MTMD) Algorithm which was later reÂ¯ned to become another algorithm named the Mass Transfer Steady State (MTSS) Algorithm. The improved forward models, consisting of a system of multivariate equations, successfully calculate the amount of mass transfer from the continuous phase to the dispersed phase and was validated by the simulation results.